2020
DOI: 10.2147/copd.s234241
|View full text |Cite
|
Sign up to set email alerts
|

<p>A Nomogram for Predicting Severe Exacerbations in Stable COPD Patients</p>

Abstract: Objective: To develop a practicable nomogram aimed at predicting the risk of severe exacerbations in COPD patients at three and five years. Methods: COPD patients with prospective follow-up data were extracted from Subpopulations and Intermediate Outcome Measures in COPD Study (SPIROMICS) obtained from National Heart, Lung and Blood Institute (NHLBI) Biologic Specimen and Data Repository Information Coordinating Center. We comprehensively considered the demographic characteristics, clinical data and inflammati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…Post-bronchodilator spirometry: Recommended in clinical guidelines to be used in conjunction with clinical assessment to confirm the diagnosis of COPD, 3,22 and is incentivized as part of the 20 and included in several risk prediction tools and models to determine exacerbation risk and/ or mortality risk. 39,40 Low BMI (ie, <21.75 kg/m 2 ) has been associated with increased risk of pneumonia and mortality in COPD patients. 41,42 Obesity, with BMI >30 kg/m 2 , is a risk factor for the development of type II diabetes, 43 a relevant comorbidity for those who frequently exacerbate and require oral corticosteroids (OCS).…”
Section: Supporting Evidencementioning
confidence: 99%
“…Post-bronchodilator spirometry: Recommended in clinical guidelines to be used in conjunction with clinical assessment to confirm the diagnosis of COPD, 3,22 and is incentivized as part of the 20 and included in several risk prediction tools and models to determine exacerbation risk and/ or mortality risk. 39,40 Low BMI (ie, <21.75 kg/m 2 ) has been associated with increased risk of pneumonia and mortality in COPD patients. 41,42 Obesity, with BMI >30 kg/m 2 , is a risk factor for the development of type II diabetes, 43 a relevant comorbidity for those who frequently exacerbate and require oral corticosteroids (OCS).…”
Section: Supporting Evidencementioning
confidence: 99%
“…GraphPad Software Inc., CA) was used to analyze differences by one-way analysis of variance and to generate graphs. p < 0.05 was considered to indicate statistical significance 22.…”
mentioning
confidence: 99%
“…Women with COPD have a higher prevalence of low BMI than their male counterparts [ 59 ]. Indeed, previous studies have shown that COPD subjects with low BMI have a shorter period of survival [ 99 ] and a greater risk of acute exacerbations with worse airflow limitation, higher level of inflammation biomarkers and poorer health status [ 100 ].…”
Section: Discussionmentioning
confidence: 99%